(3HOGjI GdeMJGL aj TQM GdefgGLs - (3eMeO Hf CHj HcQ Hf CMeO Hf eMeO, CHh GdaVd, HOQ GdOjf GdCSOj GdTGaYqj, GdeYQha cSdag HGHf bGVj TgHI , (B874 (3g` s; (3jMji Hf TQa Hf oepqQj Hf MSf GdMRGej GdMhQGfj, Gdfhhj, GdTGaYqj, CHh RcQjG, eMjj GdOjf,J (B676 (3g` s ((3YHO Gddg Hf Ydi Hf YHO Gddg Hf CMeO GdYHGOdi s)
(3ChdgG (B:s
(3GdMeO ddg Gdehab dWdH GdYde hJMUjdg , hHYO abO ESJNQJ Gddg JYGdi ai cJGHI TQM eNJUQ Ydi GdefgGL ai Gdabg dTjN GdESdGe hSejJ HOGjI GdeMJGL ai TQM GdefgGL s
(3BNQgG (B:s
(3Rdcf eQGOg GdJHGjf NGUI , hdgPG aSQ cdGeg cdGJg , hbO UQM GdahQGfi HYOe eLF GdJOGNd hGdJeGKd , hGdMeO ddg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJH GdeJf HGdMeQI s
(3Ydi ghGeTgG JbjjOGJ hJUMjMGJ s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
Keywords: (3Gdabg GdTGaYjs